Electrocatalytic Oxidation of Cellulose at a Gold Electrode. Issue 8 (6th June 2014) - Sugano, Yasuhito; Latonen, Rose‐Marie; Akieh‐Pirkanniemi, Marceline; Bobacka, Johan; Ivaska, Ari
Abstract The electrochemical properties of cellulose dissolved in NaOH solution at a Au surface were investigated by cyclic voltammetry, FTIR spectroscopy, the electrochemical quartz crystal microbalance technique, and electrochemical impedance spectroscopy. The reaction products were characterized by SEM, TEM, and FTIR and NMR spectroscopy. The results imply that cellulose is irreversibly oxidized. Adsorption and desorption of hydroxide ions at the Au surface during potential cycling have an important catalytic role in the reaction (e.g., approach of cellulose to the electrode surface, electron transfer, adsorption/desorption of the reaction species at the electrode surface). Moreover, two types of cellulose derivatives were obtained as products. One is a water‐soluble cellulose derivative in which some hydroxyl groups are oxidized to carboxylic groups. The other derivative is a water‐insoluble hybrid material composed of cellulose and Au nanoparticles (≈4 nm). Furthermore, a reaction scheme of the electrocatalytic oxidation of cellulose at a gold electrode in a basic medium is proposed.